Contrasting realities: corporate environmental disclosure and stakeholder-released information. Issue 1 (2nd January 2014) - Rodrigue, Michelle
Abstract : Purpose: – This paper aims to study the informational dynamics that take place between a firm and its stakeholders with respect to corporate environmental management. Design/methodology/approach: – The analysis is based on a case study contrasting environmental information reported by the case firm with environmental information about the firm disclosed by four stakeholder groups or their representatives (governments, the community, environmental non-governmental organizations and investors) over three years. The information flow of disclosure is also considered. Findings: – The results suggest that the informational dynamics are composed of multiple related patterns. The patterns range from correspondence between disclosures to stakeholders complementing or contradicting corporate disclosures. Different patterns are associated with different levels of interactions from stakeholders, who are most involved when they combine disclosure patterns around key environmental issues for the forest industry. Limited interactions are observed from the firm, suggesting a symbolic engagement within the dynamics and a strategic accountability approach. Research limitations/implications: – Limitations are found in the focus on disclosure outlets without examination of their production and reception, and in the inherent nature of the documents collected to represent each perspective. Some stakeholder groups were excluded from the study due to data unavailability. Originality/value: – This paper offers an in-depth analysis of firm-stakeholders interactions with respect to environmental reporting and maps the information flow of their disclosure.